(3GdSjGOI GdGSJKeGQjI (B:s (3Odjd GdGaQGO dbhI GdKQhI (B/s - (3GdMeOGf, eGLOs ((3HjQhJ(B: s (3OGQ GdaGQGHj(B, s, 2009)
(3fXQjI GdYde h GdKQhI h GdbhI h Jchjf GdhYj GdeGdj , GdJNWjW GdGSJQGJjLj GdTGed , GOGQI GdGSJKeGQ GdYGdej , CfhGY GdeSJKeQjf h GdWHbGJ GdeGdjI , YHbQjI GdUjZ h eLGdGJ GdGSJKeGQ , bhI GdJShjb h EOGQI GdeTQhY h Jehjdg, OQGSI GdLOhi GdJShjbjI GdGbJUGOjI h CNjQG bhGfjf GdPcGA GdGSJKeGQj(B.s
(3eQGLY U(B.417 (3; edGMb U(B.409s
Keywords: (3GdESJKeGQs; (3GdJMdjd GdeGdjs; (3GdJNWjWs